2024
DOI: 10.1021/acs.analchem.3c03462
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Surface Chemistry on Emulsion–Electrode Interactions and Electron-Transfer Kinetics in the Single-Entity Electrochemistry

Minshu Du,
Lizhu Zhang,
Yao Meng
et al.

Abstract: Single-entity electrochemistry (SEE) provides powerful means to track a single particle, single cell, and even single molecule from the nano to microscale. The electrode serves as not only the detector of collision but also the surface supplier in SEE, and the fundamental understanding of the electrode surface chemistry on the dynamic particle−electrode interactions and electrochemical responses of a single particle still remains unexplored, particularly for soft particles. Herein, dynamic interactions of micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…This approach allows for atomic restructuring and dynamic changes to chemical reactivity to be monitored as the applied electrochemical potential is cycled. In a different approach, Du et al formed Nile Red-doped emulsions of nitrobenzene in water, allowing SE collisions to be imaged using fluorescence microscopy . Electrochemical data of the collision of the emulsions with either gold or carbon ultramicroelectrodes showed a difference in the number of collisions and electron-transfer kinetics based on the electrode material.…”
Section: Single-entity Opto-electrochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…This approach allows for atomic restructuring and dynamic changes to chemical reactivity to be monitored as the applied electrochemical potential is cycled. In a different approach, Du et al formed Nile Red-doped emulsions of nitrobenzene in water, allowing SE collisions to be imaged using fluorescence microscopy . Electrochemical data of the collision of the emulsions with either gold or carbon ultramicroelectrodes showed a difference in the number of collisions and electron-transfer kinetics based on the electrode material.…”
Section: Single-entity Opto-electrochemistrymentioning
confidence: 99%
“…In a different approach, Du et al formed Nile Red-doped emulsions of nitrobenzene in water, allowing SE collisions to be imaged using fluorescence microscopy. 231 Electrochemical data of the collision of the emulsions with either gold or carbon ultramicroelectrodes showed a difference in the number of collisions and electron-transfer kinetics based on the electrode material. Fluorescence microscopy data revealed that the slower electron-transfer kinetics and reduced number of collisions on the carbon ultramicroelectrode surface were due to the adsorption and coalescence of the emulsions, which formed a thin organic layer that blocked the surface of the electrode, slowing electron-transfer rates in subsequent collision events.…”
Section: Single-entity Opto-electrochemistrymentioning
confidence: 99%